6G endogenous security:architecture and key technologies - Yang LIU; Mugen PENG (Dianxin kexue)
At the beginning of design for the traditional mobile communication systems,security is considered as an independent technology,relying on “patch” and “plug-in” to realize the security protection of wireless communica-tion.The sixth-generation (6G) mobile communication system is designed based on software-defined slicing platform,edge computing,artificial intelligence and big data mining to adapt to different application scenarios and performance objectives,making the traditional network security mechanisms difficult to guarantee 6G's requirements for embed-ded security.6G endogenous security was proposed,the architecture and key technologies of 6G endogenous security were described,the security threats in the new technologies were discussed which 6G would adopt,and the chal-lenges and future research directions of 6G endogenous security were provided.